The effectiveness of an FMCG Company’s employer branding practices: Can social media be used to generate better hires? - Tanha, Esha Alam (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.